Knowledge, attitude, and practice toward the prevention of occupational exposure in public health emergencies among nurses in Wuhan - Yan Liu; Zhili Zhang; Ying Liu (Frontiers Media S.A., 2024)
Background and objectiveNurses have an essential role in dealing with public health emergencies (PHE). This study explored the knowledge, attitude, and practice (KAP) towards preventing occupational exposure in PHE among nurses in Wuhan.MethodsThis cross-sectional study was conducted in May 2023 to assess the KAP of nurses in Wuhan, China. Questionnaires were created and distributed to evaluate the KAP of nurses and explore the factors associated with KAP. Univariate and multivariate logistic regression analyses were used to assess the association between baseline demographic characteristics and KAP, and structural equation modeling (SEM) was used to explore complex relationships and causal pathways among relevant factors.ResultsA total of 440 valid questionnaires were collected. The mean knowledge, attitude, and practice scores were 11.84 ± 2.37, 39.87 ± 3.10, and 44.05 ± 3.76, respectively. The univariate and multivariate logistic regression analyses revealed that age >50 years old (p = 0.039), working experience of 1-3 years (p = 0.060) and 4-6 years (p = 0.024), participation in PHE training, and scene rescue (p < 0.001) were significantly associated with knowledge score. In addition, the attitude of the nurses was significantly related to knowledge scores (p = 0.002). Moreover, practice was significantly associated with knowledge scores (p = 0.005) and attitude scores (p < 0.001). The correlation analysis showed that the practice was significantly associated with knowledge (r = 0.336, p < 0.001) and attitude (r = 0.449, p < 0.001).ConclusionNurses exhibited moderate knowledge, relatively positive attitude, and practice, which needed to be improved regarding occupational exposure in PHE. The practice of the nurses could be promoted by paying more attention to the working experience, participation in training and scene rescue in PHE, and their knowledge and attitude.